An industrial quality control study on Marsman Drysdale Food Corporation - Pontigon, Randy Jr; Reyes, Cheryl; Ventura, Rodelyn
Marsman Drysdale Food Corporation is the only manufacturing company in the country that owns a cryogenic plant and the only company that exports Philippine mangoes to Japan, Hongkong, Korea, Australia and the United States. That is why the company makes sure the Drysdale mangoes go through a series of stringent quality control measures to ensure only the best export quality mangoes get the Marsman Drysdale's name. Although the processed product in cryogenic has the highest share of Marsman Drysdale's revenue, it also consumes a high raw material and labor expense due to a high percentage of rejects. The group's primary concerns in conducting a statistical quality/process control in Marsman Drysdale is to provide recommendations for the improvement of the current system of the company by determining major problem areas in production process, establishing control chart and by performing process capability analysis to determine if the processes are able to meet company's set standards. The study focuses only on the production of frozen mangoes using cryogenic process. Using Pareto charts and Ishikawa Diagram, the main problem of the company was determined to be the low yield rate due to high percentage of nonconforming. The causes of rejections determined in the duration of the study are shipping, handling and diseases. After the application of the statistical quality characteristics of mangoes was established for monitoring process. After establishing an in-control chart, Process Capability Index/Potential Analysis is performed. The results imply that the production of frozen mangoes use too much of the specification band which is an indication of high process fallouts. Also, the company has tight acceptance sampling, which is actually acceptable for sensitive products such as food. The company sometimes sets their specifications with regards to TSS, % Acidity and PH but mostly customers particularly from other countries give their own specification. An since specification varies a lot recommendations are made on how to attain this without causing too much rejects and incurring any additional cost. To address the main problem of the company, the two main recommendations are the selection of the best suppliers and the use of control charts for monitoring processes. Implementation plan is provided for each recommendation.